2003
DOI: 10.1161/01.cir.0000066908.82782.3a
|View full text |Cite
|
Sign up to set email alerts
|

Promoter (4G/5G) Plasminogen Activator Inhibitor-1 Genotype and Plasminogen Activator Inhibitor-1 Levels in Blacks, Hispanics, and Non-Hispanic Whites

Abstract: Background-The 4G/5G polymorphism of the plasminogen activator inhibitor-1 (PAI-1) gene has been related to cardiovascular disease. Methods and Results-Insulin resistance was measured with a frequently sampled intravenous glucose tolerance test in the Insulin Resistance Atherosclerosis Study (IRAS), and PAI-1 4G/5G promoter genotype was established by allelespecific polymerase chain reaction amplification of genomic DNA. There were 287 subjects with the 4G/4G genotype (18.4%), 691 heterozygote subjects (44.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
99
4
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 60 publications
12
99
4
3
Order By: Relevance
“…Our results are comparable with those of others who found no significant association between the 4 G/5 G polymorphism and plasma levels of PAI-1 in diabetic or non-diabetic patients (Mansfield et al 1995b, Matsubara et al 1999, Festa et al 2003. In addition, Van Harmelen et al (2000) reported that PAI-1 secretion from abdominal subcutaneous adipose tissue is not influenced by the polymorphism.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are comparable with those of others who found no significant association between the 4 G/5 G polymorphism and plasma levels of PAI-1 in diabetic or non-diabetic patients (Mansfield et al 1995b, Matsubara et al 1999, Festa et al 2003. In addition, Van Harmelen et al (2000) reported that PAI-1 secretion from abdominal subcutaneous adipose tissue is not influenced by the polymorphism.…”
Section: Discussionsupporting
confidence: 90%
“…Third, it may be explained by the differences in genetic factors between these ethnic groups. Subjects homozygous for the 4G allele at position -675 in the promoter have higher PAI-1 levels 33 and ethnic differences in the distribution of 4G/5G polymorphism have been reported 6 . Although our study did not conduct genotyping, one mechanism for lower PAI-1 levels in Americans may be explained by lower prevalence of 4G/4G genotype in Americans compared to the Japanese 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Festa et al reported that blacks had lower PAI-1 levels and Hispanics had higher PAI-1 levels compared to non-Hispanic whites even after adjustment of waist, insulin sensitivity and other associated factors 6 . Iso et al reported a decade ago that Americans had higher PAI-1 levels as well as higher cholesterol levels compared to Japanese 7 .…”
Section: Introductionmentioning
confidence: 99%
“…36 Additional data also show that PAI-1 levels were lower among blacks than among whites and Hispanics and that there was an association between the PAI-1 4G/5G polymorphism and serum levels of PAI-1, as well as with ethnicity. 37 These data further emphasize the need for large-scale prospective data that investigate the interrelations between novel markers of thrombosis and inflammation and cardiovascular disease across ethnic groups.…”
Section: Novel Cardiovascular Risk Factorsmentioning
confidence: 96%